(untitled) (Journal of the College of Basic Education, 2025)
Pleurotus ostreatus powder (PO) (local strain) was added at concentrations (0, 5, 10, 15, 20%) to wheat flour used for bread production to increase its nutritional value and enhance its shelf life for the longest possible time at a temperature of (22±3°C). The research results showed that the percentage (15 and 20%) was significantly better in reducing the total live bacteria count (TVC), total coliform bacteria count (TCC) and total fungal count (TFC) compared to the control sample (without adding control). In an attempt to compare the chemical composition of the PO mushroom powder and wheat flour by estimating the percentages of moisture, protein, fat and ash, it was found that the mushroom powder contains a high percentage of proteins (31.3%) and ash (7.7%). This was clearly evident in the bread samples prepared when studying their chemical composition, as a decrease in the percentage of moisture and carbohydrates and an increase in the percentage of protein, ash and fat were recorded when the addition percentage increased. When studying the properties The sensory characteristics of the samples showed that all proportions were acceptable except for the fifth sample. The addition of Pleurotus ostreatus (PO) powder has achieved an excellent qualitative leap in the bread industry, especially in poor countries.